2014
DOI: 10.1080/17565529.2014.902355
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying drivers of household coping strategies to multiple climatic hazards in Western Uganda: implications for adapting to future climate change

Abstract: This paper investigates what drives household coping strategies in rural Uganda under different climatic hazards. Rural households in sub-Saharan Africa draw on various coping strategies to reduce the impact of climatic hazards on their livelihoods. Research to date provides only limited understanding of how the coping strategy portfolio of changes depending on the climatic stress. Using empirical data from Uganda, this research contributes to this gap by 1) exploring how household coping strategy relates to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 44 publications
4
60
1
Order By: Relevance
“…Where the wider adaptation literature has established that there are underlying causes of vulnerability (Adger, 2006), double exposure of stress factors (Berman et al, 2015) and socio-economic relationships (Adger, Arnell, et al, 2005), we find evidence to an indeterminate and complex mesh of factors that shape the present state and future vulnerability in river basin ecosystems. This is possible due to the presence of multiple exposures of physical, social, economic and political factors, apart from climate variability and environmental trends, that reinforce, transform or weaken the existing patterns of adaptive capacity of local people.…”
Section: Interactions Between Multiple Vulnerability Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Where the wider adaptation literature has established that there are underlying causes of vulnerability (Adger, 2006), double exposure of stress factors (Berman et al, 2015) and socio-economic relationships (Adger, Arnell, et al, 2005), we find evidence to an indeterminate and complex mesh of factors that shape the present state and future vulnerability in river basin ecosystems. This is possible due to the presence of multiple exposures of physical, social, economic and political factors, apart from climate variability and environmental trends, that reinforce, transform or weaken the existing patterns of adaptive capacity of local people.…”
Section: Interactions Between Multiple Vulnerability Factorsmentioning
confidence: 95%
“…Research points out that understanding capacity, vulnerabilities, coping strategies of both people and the responsible institutions is vital for designing disaster preparedness and adaptation strategies (Adger, 2006;Adger, Arnell, & Tompkins, 2005;Bandaragoda, 2006;Burrel, Davar, & Hughes, 2007;Grothmann & Patt, 2005). As coping strategies of vulnerable people are as ever changing as risk itself (Berman, Quinn, & Paavola, 2015), research on the stakeholder perspectives on vulnerability and adaptation options can provide a deeper insight into mobilizing support and adaptation investment at the appropriate level.…”
Section: Introductionmentioning
confidence: 98%
“…Berman et al (2013), Adeniji-Oloukoi et al (2013) and Chigavazira (2012) observed a correlation between population socioeconomic characteristics and adoption of coping strategies. For example, Berman et al (2013) reported that access to resources, credit and agricultural extension services and behavioural factors such as risk perception are core elements that influence a household's choice of coping stratagem. Similarly, Bryan et al (2009) and noted that entrepreneurial capacity and prevailing market systems have effects on households' choice of coping strategy.…”
Section: Determinants Of Adaptationmentioning
confidence: 99%
“…For example, access to food emergency relief was shown to negatively influence the decision to plant trees as a coping strategy in Kenya. Similarly, Berman et al (2013) and Quinn et al (2011) reported lack of technical knowledge and of access to markets as major constraints to adoption of coping strategies at rural community level. For example, in regions where only maize is eaten, lack of markets for sorghum might limit the adoption of sorghum cultivation as a drought-resistant plant.…”
Section: Constraints To Adaptationmentioning
confidence: 99%
“…In Bangladesh, farmers have worked in the garment and textile industries and performed wage labor when crops failed (Rakib, Rahman, Akter, & Bhuiyan, 2014). This suggests that rural farmers relying on market-oriented livelihoods adopt different coping strategies during a crisis than those who rely on customary farm-based livelihoods (Berman, Quinn, & Paavola, 2013).…”
Section: Introductionmentioning
confidence: 99%